Brownies daun kelor dan tempe tinggi protein serta zat besi bagi ibu hamil anemia - Arie Nugroho; Antun Rahmadi; Sutrio Sutrio; Adinda Juwita Sari (AcTion: Aceh Nutrition Journal, 2023)
Indonesia has a significant problem with iron deficiency or anemia in pregnant women. Therefore, alternatives to iron supplementation are needed to prevent iron nutritional anemia. The study aimed to assess the organoleptic acceptance and nutritional value (proximate test, Fe and Energy) of moringa brownie cake substituted with tempeh flour. The research design used a Randomized Control Trial (RCT) design with five replications. Brownies and organoleptic tests were made at the Nutrition Laboratory of the Tanjungkarang Health Polytechnic. Proximate, iron, and energy tests were conducted at the POLINELA Agricultural Technology Laboratory in 2021. Moringa leaves were added to the brownies. There are five treatments with different compositions in brownies, namely 100%:0 (F1), 85%:15 (F2), 75%:25 (F3), 65%:35 (F4), and 55%:45 (F5). Data processing was done organoleptically. Data analysis used the ANOVA test and DMRT test. The results showed that the best and most preferred brownie cake was in formula F3 (p= 0,007) with a 75% wheat flour ratio: 25% tempeh flour. The best brownie cake has a nutritional content of 21,08% water; 23,41% fat; 5,53% protein; 1,15% ash; 1,17% crude fiber, and 49.64% carbohydrates, Fe value of 10.2 mg, an energy value of 492 kcal/100g. In conclusion, substituting tempeh flour affects the organoleptic test of various moringa brownies. The best moringa brownie cake was obtained in formulation F3.